Reporting Quality in Qualitative Research Using Artificial Intelligence and the COREQ Checklist: A Systematic Review of Tourism Literature - Hacı Mehmet Yıldırım; Alparslan Güvenç; Busenur Can (International Journal of Qualitative Methods)
In the field of tourism, where quantitative methods are widely preferred as an interdisciplinary science, it is common for qualitative research to be handled with quantitative research designs and approaches. This situation raises questions about the quality of the studies. This study aims to determine the level of attention paid to the points that should be considered in the reporting of qualitative research in the field of tourism. In this context, the systematic review approach, which enables the systematic evaluation of the information available in the literature on a subject, was adopted. Accordingly, the COREQ checklist, one of the reporting criteria for the evaluation of qualitative research, was used. Within the scope of the research, 75 studies published in journals indexed in the TR Index in 2023 in the field of tourism were evaluated. A Custom GPT based on GPT-4o was created for the evaluation of the studies according to the COREQ checklist. As a result of the study, it was determined that the information based on the COREQ criteria was not sufficient in the studies examined, and the studies were inadequate, especially in terms of method and theory.